Profil Sosiodemografi dan status Kesehatan Ibu Hamil dengan Hipertensi di Kota Manado - Meo, Maria Lupita Nena; Paat, Karnia; Kundre, Rina M (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Background: Hypertension during pregnancy is a high-risk condition that poses threats to the health of both mother and baby. Objective: This study aims to describe the sociodemographic profile and health status of pregnant women with hypertension in Manado, Indonesia. Methods: This descriptive study was conducted at community health centers with high cases of pregnancy-induced hypertension, involving 44 pregnant women selected through purposive sampling. The results showed that the majority of respondents were aged 26-35 years (45.5%), were married (77.3%), and worked as housewives (84.1%), with 93% having an income below the provincial minimum wage. Educational level was predominantly high school graduates (52.3%), with most respondents experiencing hypertension starting at 20-26 weeks of pregnancy (77.3%) and 84.1% categorized as having grade 1 hypertension. Body Mass Index (BMI) showed that 52.3% of respondents were classified as overweight or obese. These findings indicate significant risk factors for hypertension, such as maternal age, socioeconomic status, and BMI, with hypertension onset occurring in the second trimester. Conclusion: The study recommends regular blood pressure monitoring, weight management, and proper health education to improve self-care and reduce hypertension-related complications in high-risk pregnant women